(untitled) (Research, Society and Development, 2020)
The objective was to analyze the scientific productions available in the literature on the care of newborns at risk in the context of the follow-up program. This is an integrative literature review carried out in the CINAHL, LILACS, MEDLINE / PubMed, Scopus and Web of Science databases, in February 2020. Twelve studies were selected, nine of which were quantitative and three qualitative, grouped into three categories: health conditions of newborns monitored by the follow-up program; factors that influence adherence and dropout from the follow-up program; nursing care in the follow-up program. This review points to a notable need to expand activities on the persistence of care for newborns discharged from neonatal units and on the follow-up program, in order to be subsidiary and can overcome the difficulties pointed out by the researches analyzed.